2019
DOI: 10.2478/s11756-019-00386-w
|View full text |Cite
|
Sign up to set email alerts
|

The possible regions to design Human Papilloma Viruses vaccine in Iranian L1 protein

Abstract: Human Papilloma Virus (HPV) genome encodes several proteins, as L1is major capsid protein and L2 is minor capsid protein. Among all HPV types HPV-16 and HPV-18 are the most common high-risk HPV (HR-HPV) types globally and the majority of cases are infected with these types. HPV entry and the initial interaction with the host cell are mainly related to the L1 protein which is the main component of HPV vaccines. The aim of this research was comparison analysis among all Iranian L1 protein sequences submitted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The L1 protein plays a major role in the receptor binding of HPVs to host cells [5]. L1 protein is the main component of the current HPV prophylactic vaccines, and the variation of its protein sequence is closely related to the effectiveness of the vaccines [46]. Due to the complex design of the multivalent L1-VLP vaccines, the vaccines cannot prevent all types of HPV infection, and some HPVs that can cause mucosal cancer cannot be covered.…”
Section: Resultsmentioning
confidence: 99%
“…The L1 protein plays a major role in the receptor binding of HPVs to host cells [5]. L1 protein is the main component of the current HPV prophylactic vaccines, and the variation of its protein sequence is closely related to the effectiveness of the vaccines [46]. Due to the complex design of the multivalent L1-VLP vaccines, the vaccines cannot prevent all types of HPV infection, and some HPVs that can cause mucosal cancer cannot be covered.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the amino acid sequence analysis of L1 protein showed that amino acid substitution was observed in three position: 176 (threonine‐to‐asparagine), 266 (threonine‐to‐alanine), and 353 (threonine‐to‐proline). Although, L1 protein is highly conserved across HPV 16 variants but amino acid substitution in this region seemed to affect recognition by neutralizing antibodies and the expression level of the L1 protein which in turn has an important effect on HPV vaccines development 21 . Studies showed that mutations on the FG Surface Loop of HPV‐16 L1 protein can lead to generate a new serotype and affect recognition by both type‐specific neutralizing antibodies and cross‐reactive antibodies 20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…to specific residue in the protein that alters the charge and the structure of the protein. NetPhos [ 11 , 12 ], DISPHOS [ 13 , 14 ], and NetPhosK [ 15 , 16 ] were performed to assess the kinas specific phosphorylation sites in INT proteins, and SCRATCH [ 13 ], DIANNA [ 14 ], VADAR [ 17 ], DbD2 [ 18 ], and PIC server [ 19 ] were used to define the disulfide bonds. Disulfide post-modification analyses showed that mutations might impact the number of bonds and bond patterns.…”
Section: Methodsmentioning
confidence: 99%